Stress perception following childhood adversity: Unique associations with adversity type and sex. (February 2020) - LoPilato, Allison M.; Addington, Jean; Bearden, Carrie E.; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; Mathalon, Daniel H.; McGlashan, Thomas H.; Perkins, Diana O.; Tsuang, Ming T.; Woods, Scott W.; Walker, Elaine F.
Abstract: Childhood adversity is associated with poor mental and physical health outcomes across the life span. Alterations in the hypothalamic–pituitary–adrenal axis are considered a key mechanism underlying these associations, although findings have been mixed. These inconsistencies suggest that other aspects of stress processing may underlie variations in this these associations, and that differences in adversity type, sex, and age may be relevant. The current study investigated the relationship between childhood adversity, stress perception, and morning cortisol, and examined whether differences in adversity type (generalized vs. threat and deprivation), sex, and age had distinct effects on these associations. Salivary cortisol samples, daily hassle stress ratings, and retrospective measures of childhood adversity were collected from a large sample of youth at risk for serious mental illness including psychoses ( n = 605, mean age = 19.3). Results indicated that childhood adversity was associated with increased stress perception, which subsequently predicted higher morning cortisol levels; however, these associations were specific to threat exposures in females. These findings highlight the role of stress perception in stress vulnerability following childhood adversity and highlight potential sex differences in the impact of threat exposures.